2023
DOI: 10.1039/d3nr00327b
|View full text |Cite
|
Sign up to set email alerts
|

Nonuniform-to-uniform structural transitions induced by ultrasonic vibrations

Abstract: The action of ultrasonic vibration (UV) on material flow plays an important role in determining structures and properties of welding joints. Recent experiments and numerical simulations at the millimeter scale...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 51 publications
(127 reference statements)
0
1
0
Order By: Relevance
“…They also observed a structural change from fcc to an amorphous structure during the UW process. Recently, Li et al [ 18 ] investigated UW welding of Mg–Al nanolayers according to heat and ultrasonic vibrations. They reported that structure transitions and increasement of Mg–Ag interface thickness were observed under large vibration amplitudes and low vibration frequency due to facilitation of atomic diffusion and dislocations motions.…”
Section: Introductionmentioning
confidence: 99%
“…They also observed a structural change from fcc to an amorphous structure during the UW process. Recently, Li et al [ 18 ] investigated UW welding of Mg–Al nanolayers according to heat and ultrasonic vibrations. They reported that structure transitions and increasement of Mg–Ag interface thickness were observed under large vibration amplitudes and low vibration frequency due to facilitation of atomic diffusion and dislocations motions.…”
Section: Introductionmentioning
confidence: 99%